2013
DOI: 10.1108/00251741311326626
|View full text |Cite
|
Sign up to set email alerts
|

The influence of social capital on service quality evaluation

Abstract: Abstract:Purpose: This research provides guidance for the global manager by determining the manner through which social interaction influences service quality evaluation. Furthermore, this paper explores the function of economic development in altering the role of social relationships in service quality evaluation.Design/methodology/approach: Consistent with the critical realism paradigm a multi-method design is adopted for this study. Sociologist Pierre Bourdieu"s (1986) structuralist perspective of culture i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
2
12
0
1
Order By: Relevance
“…The results of this study are in accordance with the research of Syahra (2003) which states that social capital does not always provide benefits in all situations, in certain situations social capital can provide benefits but in other situations social capital may not be useful or even cause harm. Likewise with the results of research Imrie (2013) who found that social capital has no influence on marketing strategy.…”
Section: The Effect Of Social Capital On Marketing Strategysupporting
confidence: 62%
See 1 more Smart Citation
“…The results of this study are in accordance with the research of Syahra (2003) which states that social capital does not always provide benefits in all situations, in certain situations social capital can provide benefits but in other situations social capital may not be useful or even cause harm. Likewise with the results of research Imrie (2013) who found that social capital has no influence on marketing strategy.…”
Section: The Effect Of Social Capital On Marketing Strategysupporting
confidence: 62%
“…The result of Fitriawati's research (2010) states that social capital influences marketing strategy. While Imrie (2013) found that social capital has no influence on marketing strategy.…”
Section: Introductionmentioning
confidence: 96%
“…As such the research design encompassed a series of primary data collection, i.e. surveys; followed by an interactive combination of abduction, deduction and induction involving a continual cycle of reflection using discussions with management, and relevant inter-disciplinary literature (Imrie, 2013). The three annual surveys (see sample discussion) involved questions regarding five of the concepts in the study's theoretical framework ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, personalisation refers to the importance of service providers to focus on individual needs and to customise the service. Offering highly customised solutions to customers have been found to help marketers in attracting more customers (Imrie, 2013). Kashif et al (2016) also showed that personalisation is an important dimension that influences customer satisfaction.…”
Section: Personalisationmentioning
confidence: 99%